Configurational Mechanism of Visual Discrimination - Yu A Chudina (Peoples' Friendship University of Russia (RUDN University), 2012)
The visual discrimination system of K-shaped figures is described in the article. We explored our constructed space of the K-shaped figures by means of the terms of Sokolov and Izmailov's spherical model of differentiating stimuli. The comparative analysis demonstrated that the K-shaped figures were recognized with a four-channel neuron network detecting the configurative features of the stimuli.